Childhood social isolation causes anxiety-like behaviors via the damage of blood-brain barrier in amygdala in female mice - Wu, Xiao; Ding, Zengbo; Fan, Tengteng; Wang, Ke; Li, Suxia; Zhao, Jing; Zhu, Weili (Frontiers in Cell and Developmental Biology, 2022)
Social interaction plays an essential role in species survival for socialized animals. Previous studies have shown that a lack of social interaction such as social isolation, especially in the early-life phase, increases the risk of developing mental diseases in adulthood. Chronic social stress alters blood-brain barrier (BBB) integrity and increases peripheral cytokines to infiltrate the brain, which is linked to the development of depressive-like behaviors in mice, suggesting that BBB function is crucial in environmental stimuli-driven mood disorders via increased neuroinflammation in the brain. However, the precise mechanisms of inflammation and BBB integrity underlying the behavioral profiles induced by social isolation remain poorly understood. Here we showed that chronic childhood social isolation from post-weaning for consecutive 8 weeks in female but not male C57BL/6J mice induces anxiety-like behaviors. The levels of peripheral inflammatory cytokines including interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α in the plasma of socially isolated female mice were increased. Importantly, we found decreased expression of the endothelial cell tight junction protein Claudin-5, increased BBB breakdown and microglial activation in the amygdala of isolated but not group-housed female mice. Moreover, the neuronal activity in the amygdala was increased as evidenced by c-fos positive cells, and the levels of IL-1β in the amygdala, a critical brain region for regulating social processing and interaction, were also higher in female mice exposed to social isolation. Finally, down-regulation of Claudin-5 induced anxiety-like behaviors in group-housed females and overexpression of Claudin-5 with adeno-associated virus in the amygdala to restore BBB integrity decreased subsequent anxiety-like behaviors. Together, these findings suggest that chronic childhood social isolation impaired BBB permeability and caused neuroinflammation in the amygdala by recruiting peripheral cytokines into the brain and activating microglia, consequently triggering the development of anxiety-like behaviors in female mice.